Overcoming Clinician and Parent Ambivalence: General Practitioners' Support of Children of Parents With Physical or Mental Illness and/or Substance Abuse - Hafting, Marit; Gullbrå, Frøydis; Anderssen, Norman; Rørtveit, Guri; Smith-Sivertsen, Tone; van Doesum, Karin (Frontiers in Psychiatry, 2019)
Identifying children as next of kin to ill and substance-abusing parents and giving the family necessary support is an important preventive mental health task. Most parents in the target groups consult a general practitioner (GP) several times over the years. Thus, the GP might be in a potent position to identify these children and ensure follow-up. There is a knowledge gap concerning GPs’ possibilities of helping patients’ children. Therefore, we conducted the research project Burdened Children as Next of Kin and the General Practitioner. Four sub-studies have been published/accepted. They consist of one sub-study with qualitative analysis of focus group interviews with GPs (paper 1), one with youth as next of kin (paper 2), and one with individual interviews with ill and substance-abusing parents (paper 3). The results from these sub-studies were then incorporated in a survey sent to members of a nationwide GP organization (paper 4). The aim of the present sub-study was to gain further knowledge about conditions for the encounter between GP and ill and substance-abusing parents to be supportive for the children as next of kin. The material for the present article are the four previous articles in the project. We conducted an overarching thematic content analysis of the result sections of the articles seen as a whole. We searched for statements from the GPs, the youths, and the parents about their experiences and evaluations of the needs of the children and their families, and the possibilities of accommodating these needs in general practice. The analysis shows that there is mutual ambivalence about addressing the topic of the patients’ children during consultations. This was the case although the GPs were in a good position to identify these vulnerable children, and the parents were worried about their children’s situation. Possible strategies for GPs to overcome this ambivalence are to 1) strengthen their practical competence in this topic, 2) gradually build a trusting relationship with the parents, and 3) gradually gain contextual knowledge about the family situation. GPs can do this by performing ordinary GP tasks and acknowledging the parents’ efforts to give their children good daily live